Observed spatio‐temporal changes of winter snow albedo over the north‐west Himalaya. (28th July 2016) - Negi, H. S.; Datt, P.; Thakur, N. K.; Ganju, A.; Bhatia, V. K.; Vinay Kumar, G.
ABSTRACT: This study presents the spatio‐temporal winter snow albedo analysis over different mountain ranges of north‐west Himalaya (NWH) for a period of approximately 24 years. Here we assess the temporal albedo variations in past two decades (1991–2010) in comparison to the recent 14 years (2000–2014). The field collected manual data of two representative observatories of Lower Himalaya (LH) and Great Himalaya (GH), and six automatic weather stations in LH, GH and Karakoram Himalaya (KH) were analysed. Satellite derived MODIS albedo data (MOD10A1) over these stations between 2001 and 2014 were analysed. A good correlation ( r = 0.59) was observed between monthly average MODIS retrieved albedo and field collected albedo for GH with a relative error of 11%. In past two decades, a statistically significant (99%) decreasing rate of −0.011 per year in winter snow albedo was observed over GH (1993–2010), while in recent decade (2001 onward), no statistically significant increasing trend was observed. The change in albedo of GH is attributed to winter mean air temperature, which shows a significant rise in the past two decades, but there has been a hiatus in winter mean air temperature rise in recent decade. The higher winter mean air temperature above 0 °C since beginning of the study period (1991 onward) kept albedo of moist/wet snow approximately stable in LH. Further, insignificant increasing trend of albedo was observed over KH range in recent decade, and it is attributed to persistent very low temperatures and an increase in the frequency of snowfall days. This albedo study over NWH supports the recently reported findings on Himalayan snow cover and glacier variations during different durations.